Use of the Suitability Model to Identify Landfill Sites in Lahore-Pakistan - S. Rathore; S.R. Ahmad; S.A. Shirazi (Journal of Basic & Applied Sciences, 2016)
Site selection is a vital and basic concern of solid waste management in Lahore District, Pakistan, where there is fast growing urbanization. An appropriate landfill site for management of solid waste in this district must be found, and this demands the evaluation of multiple suitability criteria. Based on the current situation of the study area, these criteria were assigned weights according to their relative importance by using the analytical hierarchy process (AHP). The weights were then used in a simple additive weighted process (SAW) to generate a hierarchy of suitable sites for landfill to resolve the solid waste issue in Lahore District. Geographic information system (GIS) environment was used to collect, manipulate, analyze and present spatial data. Each spatial characteristic was standardized to same scale of 1 to 5 where 1 is the lowest suitability and 5 is highest suitability. This work presents a GIS-based site selection methodology that provides support to decision makers for the assessment of waste management issues in Lahore District.